Evaluation of an Objective Measurement Tool for Stress Level Reduction by Individually Chosen Music During Colonoscopy—Results From the Study “ColoRelaxTone” - Walter, Steffen; Gruss, Sascha; Neidlinger, Jana; Stross, Isabelle; Hann, Alexander; Wagner, Martin; Seufferlein, Thomas; Walter, Benjamin (Frontiers in Medicine, 2020)
Background and Aims: Colonoscopy as standard procedure in endoscopy is often perceived as uncomfortable for patients. Patient´s anxiety is therefore a significant issue, which often lead to avoidance of participation of relevant examinations as CRC-screening. Non-pharmacological anxiety management interventions such as music might contribute to relaxation in the phase prior and during endoscopy. Although music´s anxiolytic effects have been reported previously, no objective measurement of stress level reduction has been reported yet. Focus of this study was to evaluate the objective measurement of the state of relaxation in patients undergoing colonoscopy. Methods: Prospective study (n = 196) performed at one endoscopic high-volume center. Standard colonoscopy was performed in control group. Interventional group received additionally self-chosen music over earphones. Facial Electromyography (fEMG) activity was obtained. Clinician Satisfaction with Sedation Instrument (CSSI) and Patients Satisfaction with Sedation Instrument (PSSI) was answered by colonoscopists and patients respectively. Overall satisfaction with music accompanied colonoscopy was obtained if applicable. Results: Mean difference measured by fEMG via musculus zygomaticus major indicated a significantly lower stress level in the music group (7.700(±5.560) µV vs. 4.820(±3.330) µV; p=.001). Clinician satisfaction was significantly higher with patients listening to music (82.69(±15.04) vs. 87.3(±15.02) pts.; p=.001). Patient´s satisfaction was higher but did not differ significantly. Conclusions: We conclude that self-chosen music contributes objectively to a reduced stress level for patients and therefore subjectively perceived satisfaction for endoscopists. Therefore, music should be considered as a non-pharmacological treatment method of distress reduction especially in the beginning of endoscopic procedures.